Patient Characteristics in Persistent Pulmonary Hypertension of the Newborn - M. T. R. Roofthooft; A. Elema; K. A. Bergman; R. M. F. Berger (Pulmonary Medicine)
Objective. To assess the impact of PPHN on mortality, morbidity, and behavioural skills. Methods. A retrospective observational study of 143 newborns with PPHN, over an 11-year period, using objective health-status data from medical records and family doctors, and subjective health status data from a standardized Child Behaviour Checklist. Results. The majority of patients were males, treated with inhaled nitric oxide had maladaptation/maldevelopment as pathophysiological mechanism and a gestational age >37 weeks. In term newborns, types of pathophysiological mechanism (𝑃<.001) and Oxygen Index (𝑃=.02) were independent predicting risk factors for PPHN-related mortality. Analysis of preexisting disease and outcome categories in term newborns showed only a significant correlation between the use of iNO and respiratory complaints (𝑃=.03), not confirmed by multivariate analysis and regression analysis. Conclusions. PPHN is a serious, often fatal condition. The incidence of PPHN in preterm newborns is high. In term survivors, PPHN had no additional role in morbidity/outcome.